The right upper lobe bronchus angle: A tool for differentiating fibrotic and non-fibrotic sarcoidosis - Salvatore, Mary; Toussie, Danielle; Pavlishyn, Nadiya; Yankelevitz, David; O'Connor, Timothy; Henschke, Claudia; Padilla, Maria (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Purpose: To evaluate the Right Upper Lobe Bronchus Angle (RUL-BA) on chest CT in patients with Stage 4 sarcoidosis and compare to others with non-fibrotic sarcoidosis. Methods: IRB approval was obtained for review of all chest CT scans performed from January 2015 through December 2017 that contained the word sarcoidosis using the computer program Montage. The most recent CT scans of 633 people were reviewed. The patients’ age and sex at the time of their most recent CT scan were recorded. The radiographic diagnosis and the Right Upper Lobe Bronchus Angle (RUL-BA) were determined by a chest radiologist with 20 years of experience. Results: The RUL-BA increased with Stage 4 sarcoidosis, measuring on average 104 degrees, compared to the average angle of 88 degrees for those without fibrotic sarcoid. More often men’s CT scans exhibited the earlier stages of sarcoidosis, and a higher number of women’s scans showed fibrotic sarcoidosis. As would be expected, scans with advanced disease were typically from older patients; however, there was no correlation between age and degree of fibrosis as measured by increasing RUL-BA. Conclusion: The RUL-BA assists radiologists in differentiating fibrotic sarcoidosis from non-fibrotic sarcoidosis. Further research will determine if the RUL-BA measurement can help differentiate fibrotic sarcoid from other fibrotic lung diseases and if the angle can be used to follow disease progression.